2018
DOI: 10.5607/en.2018.27.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Black Rice (Oryza sativa L., Poaceae) Extract Reduces Hippocampal Neuronal Cell Death Induced by Transient Global Cerebral Ischemia in Mice

Abstract: Rice is the most commonly consumed grain in the world. Black rice has been suggested to contain various bioactive compounds including anthocyanin antioxidants. There is currently little information about the nutritional benefits of black rice on brain pathology. Here, we investigated the effects of black rice (Oryza sativa L., Poaceae) extract (BRE) on the hippocampal neuronal damage induced by ischemic insult. BRE (300 mg/kg) was orally administered to adult male C57BL/6 mice once a day for 21 days. Bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The primary explanation for the impact is that anthocyanin, phenolic, and flavonoid compounds have the capacity to function as hydrogen donors and reducing agents, neutralizing ROS, and removing superoxide and hydrogen peroxide ions. Numerous studies have found that HN rice bran has two main functions in lowering oxidative stress through ( 1 ) direct interaction with ROS and ( 2 ) augmentation of antioxidant enzyme activity ( 56 57 58 59 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary explanation for the impact is that anthocyanin, phenolic, and flavonoid compounds have the capacity to function as hydrogen donors and reducing agents, neutralizing ROS, and removing superoxide and hydrogen peroxide ions. Numerous studies have found that HN rice bran has two main functions in lowering oxidative stress through ( 1 ) direct interaction with ROS and ( 2 ) augmentation of antioxidant enzyme activity ( 56 57 58 59 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have failed due to toxicity and side effects [ 17 ]. Medicinal plants have been studied as alternative preventive or therapeutic agents in various diseases including brain ischemia because of their minimal toxic effects [ 31 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cyanidin 3-O-β-glucopyranoside has a neuroprotective effect in an animal cerebral artery occlusion model [151]. In mice under conditions of transient global ischemia, anthocyanins from black rice (Oryza sativa L., Poaceae) attenuate neuronal cell death, inhibit reactive astrogliosis, and prevent loss of expression of glutathione peroxidase in the hippocampus, significantly improving memory impairment [152].…”
Section: Hypoxia/cerebral Ischemiamentioning
confidence: 99%